Generalización de dos métodos de detección de conglomerados. Aplicaciones en bioinformática. - Rodríguez Corvea, Laureano (2008)
This paper presents a modification to the temporal disease clusters methods in order to apply them to other sciences. Particular specifications are shown in Scan and temporal Grimson techniques. The original data are transformed in a binary sequence: the value “one” represents the interest category and value “zero” corresponds to all other cases. Computational transformations of the algorithms are implementedusing Mathematica Package. Besides some interesting bioinformatics applications are presented.